(untitled) (JAKPP (Jurnal Analisis Kebijakan & Pelayanan Publik), 2025)
The effectiveness of village funds in fostering accelerated welfare in rural areas has been a subject of scholarly debate in Indonesia. Concerns arise from the inadequate capacity of village officials to manage these funds effectively. Furthermore, external challenges, such as the limited ability of local communities to participate in village development planning, exacerbate the issue. Rather than promoting rapid economic growth and improved welfare, the mismanagement of village funds often leads to inefficiencies. This study examines the potential of village funds to enhance sustainable development performance, hypothesizing that when managed efficiently, these funds can stimulate sustainable progress. To examine this hypothesis, the study employs Data Envelopment Analysis (DEA), by using WinDEAP software to assess the efficiency levels of village funds. Due to limitations in data availability, we purposively selected and analysed 131 villages from a total of 8,494 villages in East Java. The results reveal that only 21 villages, or 16,0 percent, achieved a satisfactory efficiency (ԑp = 1), while 110 villages, or 83,9 percent did not. This finding has broad implications for implementing village decentralization, and the government needs to improve policies and continuously monitor village funds.